ANALYSIS OF THE INFLUENCE OF KNOWLEDGE LEVEL AND OTHER FACTORS ON COMMUNITY PARTICIPATION IN POSYANDU PASIR-BENGKOK VILLAGE, CISANGU VILLAGE IN 2023 - Junaeni, Junaeni; Yuliawati, Nanik (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Posyandu is a form of Community Resource Health Effort (UKBM) which is implemented by, from and with the community. to empower and make it easier for the community to obtain health services for mothers, babies and toddlers. Efforts to increase the role and function of Posyandu are not solely the responsibility of the government, but of all components in society, including cadres. Research Objectives: To determine the influence of the level of knowledge, education, and attitudes on community participation in Posyandu Pasir-Bengkok village, Cisangu village in 2023. Research Method: The research used is analytical with a cross-sectional observational approach, the research sample is 40 respondents, then testing will be carried out using an independent sample T test. Result: The results of this research show that there is a relationship between knowledge, education, and attitudes towards community participation in Posyandu Kampung Pasir-Bengkok Cisangu Village in 2023. Conclusions and Suggestions: There is still a lack of community participation in coming to the posyandu, this is influenced by factors of knowledge, education, behavior and attitudes. One effort to increase public awareness is to provide education regarding the importance of coming to the posyandu by health workers.